Analysis of curling team strategy and tactics using curling informatics - Otani, H.; Masui, F.; Yanagi, H.; Ptaszynski, M. (Proceedings of the 4th International Congress on Sport Sciences Research and Technology Support, 2008)
The 2015-2016 season became a historic season for Japanese curling. Japan national curling team has won a silver medal for the first time at the 46th Women`s World Championship 2016 in Canada. However, it is still necessary to work on strengthening the team performance in order to aim for the top. Such strengthening needs to include material factors such as the physical factor and the human factor, but also the strategic/tactical factor which is crucial in curling. Bradley (2009) points out the strategic/tactical factor as the most important at top level. As an example of a research aimed at supporting such strengthening of the strategic/tactical factor, Masui et al. (2016) proposed the concept of Curling Informatics. They built an environment for strategic/tactical support which makes use of ICT by allowing digitally collect and analyze game informations in real time. Specifically, as the first step of implementation they developed a digital scorebook iCE as amethod for digital collection of game information for further analysis. In this research we analyzed game information collected with iCE to establish the effective analysis for tactical support and verify the knowledge which can be obtained empirically and what kind of new knowledge can be obtained from it. We report on the new knowledge we obtained regarding the relationship between shot accuracy and difference in game scores, and difference in correlation for each level in 93 games collected during the 2013-2014 season.